Lake Chad sedimentation and environments during the late Miocene and Pliocene: New evidence from mineralogy and chemistry of the Bol core sediments. (June 2016) - Moussa, Abderamane; Novello, Alice; Lebatard, Anne-Elisabeth; Decarreau, Alain; Fontaine, Claude; Barboni, Doris; Sylvestre, Florence; Bourlès, Didier L.; Paillès, Christine; Buchet, Guillaume; Duringer, Philippe; Ghienne, Jean-François; et al.
Abstract: This study presents mineralogical and geochemical data from a borehole drilled near the locality of Bol (13°27′N, 14°44′E), in the eastern archipelago of the modern Lake Chad (Chad). Samples were taken from a ∼200 m long core section forming a unique sub-continuous record for Central Africa. Among these samples, 25 are dated between 6.4 and 2.4 Ma. Dominant minerals are clays (66% average) mixed with varying amounts of silt and diatomite. The clay fraction consists of Fe-beidellite (87% average), kaolinite, and traces of illite. Clay minerals originate from the erosion of the vertisols that surrounded the paleolake Chad. Sedimentological data indicate that a permanent lake (or recurrent lakes) existed from 6.7 until 2.4 Ma in the vicinity of Bol. By comparison with modern latitudinal distribution of vertisols in Africa the climate was Sudanian-like. Changes in the sedimentation rate suggest a succession of wetter and dryer periods during at least six million years in the region during the critical time period covering the Miocene–Pliocene transition. Highlights: Sediments are dominated by detrital clays, more or less mixed with silt and diatomite. These sediments indicate a (recurrent) lake between 6.7 and 2.4 Ma at Bol. The dominant clay is a Fe-beidellite, a feature of present-day vertisols. Vertisols near Bol suggest a Sudanian-like climate between 6.4 and 2.4 Ma. Changes in sedimentation rate suggest an alternating of wet and dry periods.